Tourist dining motivations at local restaurants: the moderating role of social media strategies - Sukanya Wareebor; Chompoonut Suttikun; Patcharaporn Mahasuweerachai (Cogent Business & Management)
This study explores the predictive relationships between tourists’ motivations (cultural experience, novelty seeking, prior knowledge, and nostalgia) and their gastronomic experiences as well as the perceived authenticity of local restaurants. It also examines the moderating role of social media strategies in the relationship between these motivations and gastronomic experiences. Using measures adapted from existing literature, data were collected from 597 participants and analyzed through structural equation modeling (SEM). The findings revealed that tourists’ prior knowledge positively influences their gastronomic experiences, which in turn positively affect the perceived authenticity of local restaurants. However, social media strategies do not moderate the relationship between tourists’ motivations and their gastronomic experiences. This study contributes to the limited adoption of cognitive appraisal theory in understanding food tourists’ experiences and provides recommendations for improving marketing strategies in the context of local restaurants.